Histories of nursing practice - Fealy, Gerard M.; Hallet, Christine E.; Dietz, Susanne Malchau (Nursing history and humanities., 2015)
'This book examines the history of nursing practice in Europe and North America. It differs from most other studies of nursing history by focusing on the actual clinical work of nurses. It explores two broad categories of nursing work: the 'hands-on' clinical work of treatment and care; and the work of health screening, health education and public health crisis management. The book contains ten detailed historical case studies of nursing practice across diverse settings in the late nineteenth and twentieth centuries. As well as examining 'what nurses did', it explores the significance and meaning of nursing work, for nurses themselves, their patients and their communities, and examines developments in practice against a backdrop of social, cultural, political and economic drivers and constraints. The book sets the history of nursing practice within time, place and context, but demonstrates remarkable commonalities and continuities across geographical and temporal borders. It presents examples of how practice made a distinct nursing contribution to the development of modern health systems and how it became a potent resource for disciplinary development. With its focus on the history of practice, this book should be of interest to academics and clinical nurses alike. It is also an ideal textbook for undergraduate nursing programmes, providing students with rich accounts of the history of their own disciplinary practice. The book is written by leading scholars of nursing history in Europe, North America and Australasia' --Back cover.